What Is Inquiry-Based Instruction? - Anna J. Warner; Brian E. Myers (EDIS, 2009)
AEC394, a 3-page illustrated fact sheet by Anna J. Warner and Brian E. Myers, introduces agricultural educators to inquiry-based education, providing definitions, examples, and reasons to adopt this teaching method. Includes useful resources. Published by the UF Department of Agricultural Education and Communication, September 2008.